Intrinsic Dynamic Nature of Neutral Hydrogen Bonds Elucidated with QTAIM Dual Functional Analysis: Role of the Compliance Force Constants and QTAIM‐DFA Parameters in Stability. Issue 8 (18th July 2018) - Nishide, Taro; Hayashi, Satoko; Nakanishi, Waro
Abstract: Invited for this month's cover picture is Professor Satoko Hayashi's group from the Faculty of Systems Engineering at Wakayama University (Japan). The cover picture shows Japanese lanterns for the Bon festival dance dangling on two ropes, and several molecular graphs with contour maps for hydrogen bonds (HBs) emerging from the lanterns. The curves of the ropes may correspond to the Δ E (energy of formation) and C ij (compliance constant) values for HBs, for which the product will be constant. Read the full text of their Full Paper at10.1002/open.201800051 . Abstract : " The intrinsic dynamic nature of various neutral hydrogen bonds (nHBs) is elucidated with quantum theory of atoms‐in‐molecules dual functional analysis (QTAIM‐DFA) by applying the perturbed structures generated by using the coordinates corresponding to the compliance force constants (Cij ), for which an inverse relationship between Cij and Δ E, the stability of the nHBs, is found, together with linear correlations between Δ E and the QTAIM‐DFA parameters …" Find out more about the story behind the front cover research at10.1002/open.201800051 .